Colloidal capsules: nano- and microcapsules with colloidal particle shells. (23rd February 2017) - Bollhorst, Tobias; Rezwan, Kurosch; Maas, Michael
Abstract : This review provides a comprehensive overview of the synthesis strategies and the progress made so far of bringing colloidal capsules closer to technical and biomedical applications. Abstract : Utilizing colloidal particles for the assembly of the shell of nano- and microcapsules holds great promise for the tailor-made design of new functional materials. Increasing research efforts are devoted to the synthesis of such colloidal capsules, by which the integration of modular building blocks with distinct physical, chemical, or morphological characteristics in a capsule's shell can result in novel properties, not present in previous encapsulation structures. This review will provide a comprehensive overview of the synthesis strategies and the progress made so far of bringing nano- and microcapsules with shells of densely packed colloidal particles closer to application in fields such as chemical engineering, materials science, or pharmaceutical and life science. The synthesis routes are categorized into the four major themes for colloidal capsule formation, i.e. the Pickering-emulsion based formation of colloidal capsules, the colloidal particle deposition on (sacrificial) templates, the amphiphilicity driven self-assembly of nanoparticle vesicles from polymer-grafted colloids, and the closely related field of nanoparticle membrane-loading of liposomes and polymersomes. The varying fields of colloidal capsule research are then further categorized and discussed for micro- and nano-scaled structures. Finally, a special section is dedicated to colloidal capsules for biological applications, as a diverse range of reports from this field aim at pharmaceutical agent encapsulation, targeted drug-delivery, and theranostics.